Effect of Constructivist-Based Teaching Strategy on Students' Computational Ability in Mathematics: A Gender Study in Port Harcourt - Ahumaraeze, Onyekachi Uchechukwu; Charles-Ogan, Gladys Ibibo (Brillo Journal, 2024)
The study investigated the effect of Constructivist-Based Teaching Strategy (CBTS) on students’ Mathematical Computational Ability (MCA). It aimed to determine the difference in MCA of students taught with CBTS and Conventional Method (CM); ascertain the difference in MCA of male and female exposed to CBTS and ascertain Interaction effect between the teaching strategy and gender on students MCA. A quasi-experimental research design was employed. A sample of 240 students was selected from a population of 21,079 from 38 Public Senior Secondary Schools in the Port Harcourt Metropolis of Rivers State, using a purposive and stratified random sample technique. Data were collected using a validated Computational Ability Test (CAT) on Probability. The experimental group used CBTS, while the control group used CM. Analysis was conducted using mean, standard deviation, and analysis of covariance at a 0.05 significance level. The findings of the study revealed that the experimental group outperformed the control group in terms of MCA, as evidenced by a statistically significant difference in mean scores. Additionally, a significant difference in the mean scores of male and female students taught probability using a CBTS was seen, and MCA of the male student was favored over that of the female student by CBTS. Additionally, a noteworthy interaction impact between gender and teaching approach in MCA was demonstrated by the results. Teachers should adopt CBTS in addition to the CM to help students become more proficient computationally.